Pelaksanaan Penyidikan Pelaku Tindak Pidana Kekerasan Seksual dalam Lingkup Keluarga di Wilayah Hukum Polresta Padang - Oktavia, Mutiara (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2023)
Currently, there are more patterns of human behavior that are not in accordance with the norms that apply in society, so that many criminal acts occur, one of which is sexual violence against children by their immediate family. One of these cases occurred in the jurisdiction of the Polresta Padang. The problems discussed are regarding the implementation of investigations carried out by Polresta Padang  investigators in handling cases of sexual violence in the family sphere, the obstacles faced by investigators in cases of sexual violence in the family sphere, and investigators' efforts to overcome the obstacles faced in cases of sexual violence in the family sphere. . This research uses an empirical juridical approach. The results of the research show that the implementation of the investigation process for perpetrators of criminal acts of sexual violence in the family sphere was carried out in stages, namely receiving reports, carrying out investigations, making arrests, summoning witnesses, making detentions, making confiscations, carrying out examinations of suspects and witnesses, and making requests for Visum Et. Repertum until the investigation is completed and submitted to the prosecutor's office. The obstacles faced during the investigation process were that it was difficult to obtain information, there were no witnesses who saw it directly, and the perpetrator ran away. Then the efforts made by investigators to overcome these obstacles were to ask for help from social workers from the Social Service to accompany the victim during the investigation process